Inclusion, Participation and the Emergence of British Chinese Websites - Parker, David; Song, Miri (Taylor & Francis, 2007)
Previous work has drawn attention to the relative absence of British Chinese voices in public culture. No one is more aware of this invisibility than British-born Chinese people themselves. Since 2000 the emergence of Internet discussion sites produced by British Chinese young people has provided an important forum for many of them to grapple with questions concerning their identities, experiences and status in Britain. In this paper we explore the ways in which Internet usage by British-born Chinese people has facilitated forms of self-expression, collective identity production and social and political action. This examination of British Chinese websites raises important questions about inclusion and exclusion, citizenship, participation and the development of a sense of belonging in Britain, issues which are usually overlooked in relation to a group which appears to be well integrated and successful in higher education.